2020
DOI: 10.1016/j.ygeno.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic signature representations of the emerging COVID-19 coronavirus and other coronaviruses: High identity and possible recombination between Bat and Pangolin coronaviruses

Abstract: Coronaviruses are responsible on respiratory diseases in animal and human. The combination of numerical encoding techniques and digital signal processing methods are becoming increasingly important in handling large genomic data. In this paper, we propose to analyze the SARS-CoV-2 genomic signature using the combination of different nucleotide representations and signal processing tools in the aim to identify its genetic origin. The sequence of SARS-CoV-2 was compared with 21 relevant sequences including Bat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…Another study, which supports the results of present finding, showed that the bat and pangolin coronaviruses were the most related to SARS-CoV-2 with 96% and 86% of identity all along the genome [ 57 ]. The comparison study from bat and pangolin by Li and his friends explains that BetaCoV/bat/Yunnan/RaTG13/2013 virus was more similar to the SARS-CoV-2 virus than the coronavirus obtained from the two pangolin samples (SRR10168377 and SRR10168378).…”
Section: Resultssupporting
confidence: 90%
“…Another study, which supports the results of present finding, showed that the bat and pangolin coronaviruses were the most related to SARS-CoV-2 with 96% and 86% of identity all along the genome [ 57 ]. The comparison study from bat and pangolin by Li and his friends explains that BetaCoV/bat/Yunnan/RaTG13/2013 virus was more similar to the SARS-CoV-2 virus than the coronavirus obtained from the two pangolin samples (SRR10168377 and SRR10168378).…”
Section: Resultssupporting
confidence: 90%
“…In terms of recombination events, our analysis revealed a plausible past recombination between animal CoVs from pangolin and bat, which has been also confirmed by similar analyses (i.e., Simplot and Recombination Identification Program (RIP) tool for recombination detection) [17,22,23]. Interestingly, we uncovered possible recombination events between sparrow and Rhinolophus blasii (bat), and the hCoV-HKU1 genome with hedgehog (Erinaceus), shedding light on another possible scenario about the origins of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 82%
“…This transformation is called “DNA coding”. In this work, we opted for a special coding technique called “Order 2 Frequency Chaos Game Signal” (FCGS 2 ) [ 23 , 24 ]. The FCGS 2 coding is a statistical representation of DNA.…”
Section: Methodsmentioning
confidence: 99%